2009
DOI: 10.1111/j.1463-1318.2009.02091.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and endoscopic characteristics of acute haemorrhagic rectal ulcer, and endoscopic haemostatic treatment: a retrospective study of 95 patients

Abstract: Understanding the typical clinical and endoscopic findings and careful endoscopic examination are important for the accurate diagnosis of AHRU, and endoscopic haemostatic therapy may be effective for bleeding patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…Previously, Motomura et al . reported that most of their patients with AHRU had hypoalbuminaemia; this is not surprising because elderly bedridden patients are generally predisposed to malnutrition due to inadequate dietary intake or underlying disorders. As malnutrition itself can impede ulcer healing , however, malnutrition may contribute to worsening of AHRU .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Motomura et al . reported that most of their patients with AHRU had hypoalbuminaemia; this is not surprising because elderly bedridden patients are generally predisposed to malnutrition due to inadequate dietary intake or underlying disorders. As malnutrition itself can impede ulcer healing , however, malnutrition may contribute to worsening of AHRU .…”
Section: Discussionmentioning
confidence: 99%
“…In our patient, other types of colitis (such as ischemic colitis, collagenous colitis or ulcerative colitis) were also suspected. The colonoscopic findings of CMV colitis are various and include various lesions, such as a solitary ulcer, multiple ulcers, ischemic colitis, polypoid lesions, pseudomembranous colitis-associated lesions and rectal ulcer (8)(9)(10)(11)(12)(13). A previous case report described an ulcerated stricture caused by CMV colitis (27).…”
Section: Discussionmentioning
confidence: 99%
“…The reported colonoscopic findings of CMV colitis include various lesions such as a solitary ulcer, multiple ulcers, ischemic colitis, polypoid lesions, and pseudomembranous colitis-associated lesions (8)(9)(10)(11)(12). When investigations into the etiology of acute hemorrhagic rectal ulcers are performed, physicians should exclude other diseases such as CMV colitis (13,14). The definitive diagnosis of CMV colitis is made based on the histological finding of inclusion bodies in enlarged cells of the mucosa and by CMV-specific immunohistochemical staining (6).…”
Section: Introductionmentioning
confidence: 99%
“…Hemostasis usually can be achieved with repeat endoscopic procedures; in refractory cases, angiographic embolization or per-anal suturing may be required. 123,124 Other causes of anorectal bleeding Less-frequent causes of anorectal bleeding include anal cancer (Fig. 12), rectal adenocarcinoma (Video 16), anal melanoma, inflammatory polyps ( Fig.…”
Section: Acute Hemorrhagic Rectal Ulcermentioning
confidence: 99%
“…123,124 The term refers to solitary or multiple rectal ulcers associated with sudden, massive, painless rectal bleeding, usually in critically ill and/or bedridden elderly patients. The pathophysiologic basis of these ulcers is believed to be related to relative rectal mucosal ischemia secondary to supine positioning, atherosclerosis, and diabetes mellitus.…”
Section: Acute Hemorrhagic Rectal Ulcermentioning
confidence: 99%